Pluralist Democracy in International Relations L.T. Hobhouse, G.D.H. Cole, and David Mitrany - Holthaus, Leonie (The Palgrave Macmillan History of International Thought, 2018)
This book demonstrates the importance of democracy for understanding modern international relations and recovers the pluralist tradition of L.T. Hobhouse, G.D.H. Cole, and David Mitrany. It shows that pluralism's typical interest in civil society, trade unionism, and transnationalism evolved as part of a wide-ranging democratic critique that representative democracies are hardly self-sustaining and are ill-equipped to represent all entitled social and political interests in international relations. Pluralist democratic peace theory advocates transnational loyalties to check nationalist sentiments and demands the functional representation of social and economic interests in international organizations. On the basis of the pluralist tradition, the book shows that theories about domestic democracy and international organizations co-evolved before scientific liberal democratic peace theory introduced new inside/outside distinctions.